The Pattern of Economic Development Policies of Presidents with Highest Electoral Accountability: Case: Nestor Kirchner and Lula da Silva - Hakim, Amri; Yandra, Alexsander; Yahya, Muhammad Rafi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
Nersto Kirchner and Lula da Silva’s highest electoral accountability was caused by their economic development success. The discursive condition for political economy of development scholars is what the economic development model which were exercised by both presidents. This article aims to find the Kirchner and da Silva’s economic development model, were there pattern of their economic policy. By using qualitative method and library research found that the both presidents to pursue economic growth by free floating exchange rate, monetary expansive, export oriented that can be abstracted as neoliberal development model, but Lula broad income redistribution and Kirchner massive minimum wage increasing policy, also food price engineering can be abstracted as dependency model.